Answer :

By using the distributive law

(i) (2xy – xy)(3xy – 5)


= 2xy (3xy – 5) –xy (3xy –5)


= 6x2y2 –10xy – 3x2y2 +5xy


= 3x2y2 – 5xy (after adding and subtracting the like terns)


(ii) (3xy2 + 1)(4xy – 6xy2)


By using the distributive law


3xy2 ((4xy – 6xy2) +1((4xy – 6xy2)


= 3xy2 × 4xy – 3xy2 × 6xy2 + 4xy – 6xy2


= 12x2y3 – 18 x2y4 + 4xy –6xy2


(iii) (3x2 + 2x)(2x2 + 3)


By using the distributive law


3x2 (2x2 + 3) +2x (2x2 + 3)


= 3x2 × 2x2 + 3x2 × 3 + 2x × 2x2 + 2x × 3


= 6x4 + 9x2 + 4x3 +6x


(iv) (2m3 + 3m)(5m – 1).


By using the distributive law


2m3 (5m –1) +3m (5m –1)


= 2m3 × 5m – 1× 2m3 + 3m × 5m – 1× 3m


= 10m4 – 2m3 + 15m2 – 3m


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Find the product:Karnataka Board - Mathematics Part I

Simplify the follKarnataka Board - Mathematics Part I